Expression and characterization of Est2: a novel cold-adapted esterase from Antarctic bacterium defining the new esterase family XXII - He, Yuanfang; Sun, Zeyuan; Zhang, Xiying; Xing, Shu; He, Hailun; Bielicki, John Kevin; Zhou, Mingyang (Frontiers in Microbiology, 2025)
Extremozymes from Antarctic microbiota represent a potential source of unique biocatalysts. In this study, a novel esterase gene est2 was identified from the Antarctic bacterium Pseudomonas sp. A6-5. Phylogenetic and sequence analyses classified it as the founding member of a new esterase family XXII. The catalytic triad of the enzyme consisted of Ser141, Asp275, and His303, with the nucleophilic Ser141 situated within the characteristic GXSXG motif of α/β-hydrolases. Est2 exhibited remarkable cold-adaptation where 20–85% of the maximum activity was observed at temperatures ranging from 0 to 15°C. Substrate specificity profiling revealed preferential hydrolysis of medium-chain p-nitrophenyl esters and triglyceride emulsions. Enzyme activity was sensitive to inhibition by transition metals (1 mM of Mn2+, Cu2+, Co2+, Ni2+ or Zn2+), but alkali metals were considerably less effective. Representative polar-protic and -aprotic solvents uniformly inhibited Est2 activity. Collectively, these results suggest the structural stability of Est2 is largely governed by hydrophobic interactions and H-bonding, rather than ionic forces. Est2 appears to represent a unique cold-adaptive enzyme that may be suitable for bio-catalyzed environmental remediation.